AB1214 Bone mineral density and t-score evaluation in a group of patients with rheumatoid arthritis using a new ultrasound method: echos – genodynamic - a pilot study –. (12th June 2018) - Decianu, R.D.; Bojinca, M.; Daia-Iliescu, S.; Mazilu, D.; Negru, M.M.; Balanescu, A.R.; Opris- Belinski, D.; Ionescu, R.; Bojinca, V.C.
Abstract : Background: There is a great need of a screening programme for osteoporosis in the general population and even more amongst the rheumatologic patients, with additional risk factors. Although DXA is the gold standard for diagnosing osteoporosis, it is not appropriate for screening, because of its' limitations regarding ionising radiation, but also the massive machine, that needs dedicated spaces and specialised operators, all in all, involving high costs. Objectives: To apply a new method that integrates ultrasonography with radiofrequency signals from an echographic scan, in order to evaluate the bone mineral density (BMD) and T-scores in patients with rheumatoid arthritis (RA), compared to a control group. Methods: We enrolled 150 menopausal women, 75 diagnosed with RA and 75 age matched controls. The controls were selected considering the lack of both an inflammatory disease and history of corticotherapy. All patients in the study group were under monotherapy with a conventional synthetic DMARD and they are or have been under corticotherapy during the evolution of RA. The BMD and T score were evaluated using a quantitative ultrasound Echolight machine. There were two evaluators for both lots, on order to minimise the inter-observer variability. Results: 13% of the patients in the study group were under corticotherapy at the moment they were recruited in the study and 87% were treated with cortisone before, at some point during the evolution of RA. The average dose followed for more than 2 weeks was 8.8 (5–15) mg prednisone/day. The average corticotherapy period of 2.6 (0.5–14) months. For the lumbar vertebrae (L1-L4), the average T score in the study group was −1.81, while the control group had a T score of −1.11. For the femoral neck, the average T score for both hips was −1.73 for the study group and −1.04 for the controls. The spine average BMD was 0.92 g/cm 2 in the study group, compared to 1.16 g/cm 2 in the control group. For the femoral neck, the study group average BMD was 0.72 g/cm 2, while in the control group it was 0.94 g/cm 2 . Conclusions: The differences between the two groups were significant, but still in the osteopenia interval. The significance of these results translates into an increased fracture risk and a longer treatment duration in the study group. At this point, this is a preliminary study, but we plan to continue it by comparing these results to DXA results for the same patients, in order to evaluate the cost-effective superiority of this portable, radiation-free technique, in a screening programme. References: [1] Casciaro S, Peccarisi M, Pisani P, et al. An Advanced Quantitative Echosound Methodology for Femoral Neck Densitometry. Ultrasound Med Biol2016; 42(6):1337–1356. [2] Aventaggiato M, Conversano F, Pisani P, et al. Validation of an automatic segmentation method to detect vertebral interfaces in ultrasound images. IET Science, Measurement & Technology 2016; 10(1):18 – 27. Disclosure of Interest: None declared